Seizures in Patients With Metastatic Brain Tumors: Prevalence, Clinical Characteristics, and Features on EEG. Issue 2 (17th March 2021) - Ajinkya, Shaun; Fox, Jonah; Houston, Peter; Greenblatt, Adam; Lekoubou, Alain; Lindhorst, Scott; Cachia, David; Olar, Adriana; Kutluay, Ekrem
Abstract : Introduction: Metastases to the brain (MB) occur in up to 30% of adults with cancer; of these, 15% to 35% may have seizures. We investigated clinical and pathologic associations with seizure and EEG findings in patients with MB, given the sparse literature in this area. Methods: We performed a retrospective chart review of adults with pathologically confirmed MB treated at a large tertiary care center between April 8, 2006, and December 14, 2018. Primary outcomes were odds of "chart-documented seizure" (CDS) in the full sample and EEG-captured seizure or any epileptiform discharges among those monitored on EEG. Results: We studied 187 patients with MB, of whom 55 (28.3%) were monitored on EEG. We found an overall CDS prevalence of 29.4% and an EEG-captured seizure of 18.9% among patients monitored on EEG. Of those monitored on EEG, 47.2% had epileptiform discharges. Adenocarcinoma pathology was associated with lower odds of CDS (odds ratio [OR] 0.50, 95% CI 0.26–0.96) and EEG-captured seizure (OR 0.09, 95% CI 0.01–0.87) versus other pathologies. When modeled separately, melanoma pathology was associated with CDS (OR 4.45, 95% CI 1.58–12.57) versus other pathologies. Hemorrhagic MB were associated with any epileptiform discharges (OR 5.50, 95% CI 1.65–18.37), regardless of pathology modeled. Increasing size of the largest dimension of the largest MB was associated with lower odds of CDS (OR 0.68, 95% CI 0.52–0.89 when adenocarcinoma modeled, OR 0.69, 95% CI 0.53–0.91 when melanoma modeled). Conclusions: Seizures and epileptiform discharges are common in patients with MB. Tumor size and pathology were significantly associated with CDS. Larger studies are needed for further analysis.